Degradation mechanisms of silicone rubber under different aging conditions. (October 2019) - Kaneko, Takuya; Ito, Seitaro; Minakawa, Takefumi; Hirai, Naoshi; Ohki, Yoshimichi
Abstract: Various kinds of aging treatments were given to silicone rubber (SiR), an important inorganic polymer for electrical insulation. Then, the SiR sheets were examined by terahertz (THz) absorption spectroscopy, infrared absorption spectroscopy, nuclear magnetic resonance, and indenter modulus. As a result, it has become clear that three degradation mechanisms appear in SiR, depending on the aging condition. If SiR is aged thermally, the formation of cross-linked structures dominates. On the other hand, the oxidation of cyclic siloxane at the surface appears obviously if SiR is gamma irradiated at room temperature. In the case of steam exposure at 155 °C, SiR loses its molecular weight by hydrolysis. Corresponding with these aging processes, specific changes appear in THz absorption spectra. Regarding this, THz absorption spectroscopy is useable for condition-monitoring of SiR. Highlights: Several analyzing measurements were conducted to SiR aged to various degrees. SiR is cross-linked by thermal aging since molecular motions are activated thermally. Formation of carbonyl groups is induced by gamma irradiation at room temperature. When SiR is exposed to steam, hydrolysis occurs and SiR loses the molecular weight. Corresponding with the aging conditions, specific changes appear in THz absorption.